Economic Valuation of Natural Resources of Oil Palm Plantations in Mandailing Natal - Purba, Bonaraja; Gultom, Rona Hinirim; Feby, Yohana; Sihombing, Theresia (Peneliti.net, 2023)
This research aims to find out the economic valuation, social and environmental impacts of oil palm plantations in Mandailing Natal, North Sumatra. This research uses secondary methods by exploring data from various sources including literature, legal documents and case studies. The research results show significant economic growth in Mandailing Natal, especially in the information and communication sector as well as the agriculture, forestry and fisheries sectors. Palm oil production experiences significant fluctuations, with social impacts including employment and environmental problems. This research provides valuable guidance for local governments, palm oil plantation companies, and stakeholders in making sustainable and balanced decisions between economic development and environmental conservation in Mandailing Natal.